A textbook of engineering and general geology - Singh, Parbin (S. K. Kataria & Sons, 2012)
A textbook of engineering and general geology / Singh, Parbin. -- New Delhi: S. K. Kataria & Sons, 2012 624.1 Si617e8 8th rev ed. No. of Copies : 1